Is it tuberculosis or is it not? - A dilemma in primary care - Jamani, Nurjasmine Aida; Abdul Azih, Muhammad Naimmuddin (ScienceForecast Publications LLC, 2019)
Pulmonary tuberculosis is a major public health concern especially in primary care. Most of the time, the diagnosis and treatment are clear-cut based on the clinical, radiological and laboratory findings. However, the management of tuberculosis in a patient can pose a challenge to the treating physician when Non-Tuberculous Mycobacterium (NTM) is cultured. This case highlights the clinical significance and treatment dilemma of NTM infection in a pulmonary tuberculosis patient from the primary care perspectives.